The Identification of Maize and Arabidopsis Type I FLAVONE SYNTHASEs Links Flavones with Hormones and Biotic Interactions - Falcone Ferreyra, María Lorena (Plant Physiol, 2015)
Flavones are a major group of flavonoids with diverse functions and are extensively distributed in land plants. There are two different classes of FLAVONE SYNTHASE (FNS) enzymes that catalyze the conversion of the flavanones into flavones. The FNSI class comprises soluble Fe(2+)/2-oxoglutarate-dependent dioxygenases, and FNSII enzymes are oxygen- and NADPH-dependent cytochrome P450 membrane-bound monooxygenases. Here, we describe the identification and characterization of FNSI enzymes from maize (Zea mays) and Arabidopsis (Arabidopsis thaliana). In maize, ZmFNSI-1 is expressed at significantly higher levels in silks and pericarps expressing the 3-deoxy flavonoid R2R3-MYB regulator P1, suggesting that ZmFNSI-1 could be the main enzyme for the synthesis of flavone O-glycosides. We also show here that DOWNY MILDEW RESISTANT6 (AtDMR6), the Arabidopsis homologous enzyme to ZmFNSI-1, has FNSI activity. While dmr6 mutants show loss of susceptibility to Pseudomonas syringae, transgenic dmr6 plants expressing ZmFNSI-1 show similar susceptibility to wild-type plants, demonstrating that ZmFNSI-1 can complement the mutant phenotype. AtDMR6 expression analysis showed a tissue- and developmental stage-dependent pattern, with high expression in cauline and senescing leaves. Finally, we show that Arabidopsis cauline and senescing leaves accumulate apigenin, demonstrating that Arabidopsis plants have an FNSI activity involved in the biosynthesis of flavones. The results presented here also suggest cross talk between the flavone and salicylic acid pathways in Arabidopsis; in this way, pathogens would induce flavones to decrease salicylic acid and, hence, increase susceptibility.